A comprehensive study and analysis of artificial intelligence-based waiter robot in restaurant - Nafis, Allama Bakhtiyar; Ahammed, Kawsar; Oishi, Humaira Rahman; Afroj, Sumya; Raka, Rezwana Chaudhury (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.